Point‐of‐care ultrasound‐first for the evaluation of small bowel obstruction: National cost savings, length of stay reduction, and preventable radiation exposure. (25th March 2022) - Brower, Charles H.; Baugh, Christopher W.; Shokoohi, Hamid; Liteplo, Andrew S.; Duggan, Nicole; Havens, Joaquim; Askari, Reza; Rehani, Madan M.; Kapur, Tina; Goldsmith, Andrew J.
Abstract: Objectives: Computed tomography (CT) has long been the gold standard in diagnosing patients with suspected small bowel obstruction (SBO). Recently, point‐of‐care ultrasound (POCUS) has demonstrated comparable test characteristics to CT imaging for the diagnosis of SBO. Our primary objective was to estimate the annual national cost saving impact of a POCUS‐first approach for the evaluation of SBO. Our secondary objectives were to estimate the reduction in radiation exposure and emergency department (ED) length of stay (LOS). Methods: We created and ran 1000 trials of a Monte Carlo simulation. The study population included all patients presenting to the ED with abdominal pain who were diagnosed with SBO. Using this simulation, we modeled the national annual cost savings in averted advanced imaging from a POCUS‐first approach for SBO. The model assumes that all patients who require surgery or have non‐diagnostic POCUS exams undergo CT imaging. The model also conservatively assumes that a subset of patients with diagnostic POCUS exams undergo additional confirmatory CT imaging. We used the same Monte Carlo model to estimate the reduction in radiation exposure and total ED bed hours saved. Results: A POCUS‐first approach for diagnosing SBO was estimated to save a mean (±SD) of $30.1 million (±8.9 million) by avoiding 143, 000 (±31, 000) CT scans. This resulted in a national cumulative decrease of 507, 000 bed hours (±268, 000) in ED LOS. The reduction in radiation exposure to patients could potentially prevent 195 (±56) excess annual cancer cases and 98 (±28) excess annual cancer deaths. Conclusions: If adopted widely and used consistently, a POCUS‐first algorithm for SBO could yield substantial national cost savings by averting advanced imaging, decreasing ED LOS, and reducing unnecessary radiation exposure in patients. Clinical decision tools are needed to better identify which patients would most benefit from CT imaging for SBO in the ED.